Polyostotic osteolysis and hypophosphatemic rickets with elevated serum fibroblast growth factor 23: A case report. (8th June 2015) - Sato, Takeshi; Muroya, Koji; Asakura, Yumi; Yachie, Akihiro; Nishimura, Gen; Aida, Noriko; Machida, Jiro; Tanaka, Yukichi; Hasegawa, Tomonobu; Adachi, Masanori
<x xml:space="preserve">Abstract</x> We report on a boy who presented with hypophosphatemic rickets with elevated serum fibroblast growth factor 23 (FGF23) and polyostotic osteolytic lesions at age 2 years. Tumor‐induced hypophosphatemic rickets was suspected; however, bone biopsy for osteolytic changes revealed no tumorous change, except for irregularly dilated vessels associated with osteoclasts and fibrous proliferation. Venous sampling failed to point to FGF23‐producing foci. After alfacalcidol and phosphate supplementation, the rachitic skeletal changes improved, but FGF23 increased and new osteolytic lesions developed. Serum levels of neopterin and a few cytokines, including plasma transforming growth factor‐β and soluble tumor necrosis factor receptor type II, were elevated. At age 4 years, high doses of phosphate resulted in increased serum phosphate levels, decreased neopterin and cytokines, decreased FGF23, and stabilization of osteolysis. We excluded germline mutations in PHEX, FGF23, DMP1, and ENPP1 (genes for hereditary hypophosphatemic rickets) and somatic mutations in the GNAS and HRAS/KRAS (the disease‐causing genes for McCune‐Albright syndrome and linear nevus sebaceous syndrome, respectively). We could not perform octreotide scintigraphy or fluorodeoxyglucose‐positron emission tomography, and thus could not completely exclude occult FGF23‐producing tumors. However, considering the course of the disease, it is intriguing to assume that dysregulation of osteoclast‐macrophage lineage may have induced increased neopterin levels, increased cytokine levels, osteolytic process, and possibly FGF23 overproduction. © 2015 Wiley Periodicals, Inc.